A study of the role of Natural food preservatives and their effectiveness to improve food safety and shelf life (International Journal of Food and Nutritional Sciences, 2022)
Food safety regulators, the food business, and consumers are all very concerned about food-borne illnesses. Natural preservatives are essential for extending the shelf life and improving food safety. Therefore, the purpose of this study was to evaluate the research on how natural preservatives may improve food safety and lengthen the shelf life of food products. According to the review study, there has been a lot of interest lately in natural antimicrobial compounds that prevent bacterial and fungal growth for higher quality and shelf life. Secondary metabolites of plants, animals, and microbes are primarily harvested and isolated as natural antimicrobials. More focus is being placed on plants as a source of natural antimicrobials, particularly herbs and spices.In addition to bacteriocins, microorganisms utilised in food fermentation also produce a variety of antimicrobial metabolites, such as organic acids, hydrogen peroxide, and diacetyl. Various antibacterial substances are present in products of animal origin, including milk and tissues.